Pentoxifylline, a nonselective phosphodiesterase inhibitor, in adjunctive therapy in patients with irritable bowel syndrome treated with mebeverine - Sahar M. El‑Haggar (Elsevier, 2022)
Background: Irritable bowel syndrome (IBS) is a functional gastrointestinal condition marked by chronic bowel pain or discomfort, as well as changes in abdominal motility. Despite its worldwide prevalence and clinical impact, the cause of IBS is unknown. Inflammation could play a fundamental role in the development of IBS. The aim of this study was to examine whether pentoxifylline, a competitive nonselective phosphodiesterase inhibitor, is useful in alleviating abdominal pain in IBS patients treated with mebeverine. Methods: A randomized, controlled, and prospective clinical study that included 50 outpatients who met the inclusion criteria for IBS. Patients are allocated randomly into two groups (n = 25). Group 1 (mebeverine group) received mebeverine 135 mg three times daily (t.i.d) for three months. Group 2 (pentoxifylline group) received mebeverine 135 mg t.i.d and pentoxifylline 400 mg two times daily for three months. Patients were assessed by a gastroenterologist at baseline and three months after the medication had been started. The serum levels of interleukin-6, interleukin-8 and tumor necrosis factor-alpha, fecal Neutrophil Gelatinase Associated Lipocalin (NGAL), and fecal myeloperoxidase were measured at the start and after three months of therapy. The Numeric Pain Rating scale (NRS) was assessed at baseline and after therapy. Results: the pentoxifylline group showed a significant decrease in the level of measured biomarkers and a significant decrease in NRS. Conclusion: Pentoxifylline could be a promising adjuvant anti-inflammatory drug in the treatment of abdominal pain in IBS patients treated with mebeverine.